Comparison of Hospital Responsibility to Medication Error in Pharmacy Services in Indonesia and Malaysia - Yudhi Kurniawan; OK. Isnainul; Sonya Airini Batubara (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
Medication errors are events that cause harm to patients due to the use of medication while being treated by health workers, which can actually be prevented. Medication errors occur very often in hospitals and have fatal consequences due to medication errors. In Indonesia and Malaysia, pharmaceutical services still need to be optimized so that the incidence of Medication Errors can be minimized. Medication errors can occur in 4 phases, namely prescribing errors, errors in translating prescriptions (transcribing errors), errors in preparing and dispensing medication (Dispensing Error), and errors in administering medication to patients (Administration Error). This research uses a Normative Juridical approach. Data was collected through literature research and using qualitative and descriptive analysis. The conclusion from this research is that hospitals have a big responsibility for the occurrence of medication errors. This has been regulated in Law No. 44 of 2009 concerning Hospitals, article 46. Pharmaceutical services in Indonesia are still not in accordance with Law Number 36 of 2009 concerning Health and Government Regulation Number 51 of 2009 concerning Pharmaceutical Work. However, the implementation is optimal. Meanwhile in Malaysia it is also not optimal. Existing law enforcement in Indonesia regarding pharmaceutical laws is good but not optimal. It is necessary to carry out trials again regarding its implementation so that later it can be carried out optimally. Meanwhile, law enforcement in Malaysia is not good enough because there is no specific law regulating pharmaceutical law enforcement.